Theory and practice of conservancies: evidence from wildlife management areas in Tanzania - Kimario, Fidelcastor F.; Botha, Nina; Kisingo, Alex; Job, Hubert (ERDKUNDE, 2020)
The integrity of Protected Areas depends on the surrounding communities and their land as they provide crucial ecological functions as wildlife corridors. Hence, the paper analyses the performance of Tanzanian Wildlife Management Areas (WMAs) to better understand their relevance for safeguarding biodiversity outside of traditional protected areas, e.g. national parks. The article assesses the potential of WMAs, which have complex social and ecological processes and interactions, to achieve their environmental and socio-economic goals from a governance perspective. Therefore, a combination of two theoretical approaches – the Social-Ecological Systems Framework (SESF) and the Sustainable Livelihoods Approach (SLA) – was employed to provide a thorough and methodical evaluation of their system dynamics. This research mainly presents data gathered in 2017 in eight fully authorised WMAs of different ages, and which represent a tourist activity gradient from no nature-based to well-developed. Qualitative empirical research included focus group discussions, field observations and semi-structured interviews with key persons and representatives of different organisations. These include local managers and members of WMAs, regional District Councils officials from the areas where the WMAs have been established, and international stakeholders. The study shows that local governance of wildlife resources in most WMAs is still plagued by understaffing, inadequate funding, insufficient skills and knowledge, and investment issues. As a result, it takes time for the tourist industry to find confidence in the WMA concept, but recent figures show that WMA related tourism facilities which are increasingly sponsored by private investors, show higher revenues. Therefore, for WMAs to be sustainable, it is imperative to address the concerns mentioned above. Community-based conservation is part of development and the improvement of the overall wellbeing of people. However, in practice, everything is still only valued in terms of direct cash benefits. Where the analysed WMAs are failing it is mostly because unsustainable revenue sources cannot provide in their daily operational needs or adequately fund community development projects. Hence, because conservation is expensive, the key to the long-term sustainability of WMAs remains impeccable governance and financial stability.